1978
DOI: 10.1021/ic50184a006
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and crystal structures at -35.degree.C of bis(.eta.3-2-allyl)-1,2-ethanobis(tricarbonylcobalt) and bis(.eta.3-2-allyl)-1,3-propanonobis((trimethyl phosphite)dicarbonylcobalt)

Abstract: The two T73-allyl complexes {(CO)3Co[(CH2)2CCH2]j2 and |(CO)3Co[(CH2)2CCH2](2CO have been prepared by reaction of (chloromethyl)allyl chloride and NaCo(CO)4 in refluxing THF. Both species are formed during this reaction and may be converted to the trimethyl phosphite derivatives by replacement of one CO ligand per Co atom. The structures of |(CO)3Co[(CH2)2CCH2]|2 and j[(CH30)3P](CO)2Co[(CH2)2CCH2]j2CO have been determined by single-crystal x-ray diffraction techniques with three-dimensional data gathered at -3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The structures of the mononuclear (C 3 H 5 )­Co­(CO) n ( n = 3, 2, 1) were optimized by the same DFT methods (Figure ). The only low-lying structure predicted for C 3 H 5 Co­(CO) 3 is the singlet C s structure (η 3 -C 3 H 5 )­Co­(CO) 3 known experimentally. , The predicted Co–C distances and the ν­(CO) frequencies are comparable to the experimental values. The only structure obtained for C 3 H 5 Co­(CO) 2 is also a C s singlet (η 3 -C 3 H 5 )­Co­(CO) 2 structure.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The structures of the mononuclear (C 3 H 5 )­Co­(CO) n ( n = 3, 2, 1) were optimized by the same DFT methods (Figure ). The only low-lying structure predicted for C 3 H 5 Co­(CO) 3 is the singlet C s structure (η 3 -C 3 H 5 )­Co­(CO) 3 known experimentally. , The predicted Co–C distances and the ν­(CO) frequencies are comparable to the experimental values. The only structure obtained for C 3 H 5 Co­(CO) 2 is also a C s singlet (η 3 -C 3 H 5 )­Co­(CO) 2 structure.…”
Section: Resultsmentioning
confidence: 58%
“…All of the low-energy binuclear TMECo 2 (CO) n ( n = 6, 5, 4, 3) structures have the TME moiety functioning as a bis­(trihapto) ligand, thus bonding to each cobalt atom in a similar manner to the allyl–cobalt bond in the well-known ,, (η 3 -C 3 H 5 )­Co­(CO) 3 . For the two low-energy structures 2S-1 and 2S-2 of the more highly unsaturated TMECo 2 (CO) 2 , the TME moiety functions as a bis­(tetrahapto)­ligand with the two “central” TME carbons bonded to both cobalt atoms (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Scheme , HCo­(CNAr Mes2 ) 4 ( 1 ) reacts with 1,3-cyclohexadiene (1,3-CHD), 1,4-cyclohexadiene (1,4-CHD), 1,3-cyclooctadiene (1,3-COD), and cyclooctatetraene (COT) to exclusively form cobalt tris­(isocyanide) η 3 -π-allyl complexes (i.e., (η 3 -allyl)­Co­(CNAr Mes2 ) 3 ; 4 R , R = CDH, COD, COT) with loss of a single CNAr Mes2 ligand. Crystallographic structure determinations of complexes 4 R (Figure ) revealed that they possess a pyramidalized tris­(isocyanide) cobalt core capped by an η 3 -π-allyl interaction and overall are structurally similar to other (η 3 -allyl)­CoL 3 complexes reported in the Cambridge Structural Database (CSD; L = CO, PR 3 ). Of this series of η 3 -allyl complexes, the molecular structure of 4 COT is the most notable, as a saturated methylene group (i.e., CH 2 ) is located at the apical position of the newly formed C 8 H 9 cyclooctatrienyl ring. An a nalysis of the bond distances in 4 COT indicate that it is best described as a conjugated η 3 -allyl diene, rather than a coordinated pentadienyl fragment.…”
Section: Resultsmentioning
confidence: 73%
“…The composition of 1 − 3 deduced from the stoichiometry of their formation according to eqs 1−3 could be verified by osmometric molecular weight determination of the isolated complexes. The 13 C NMR spectra of the complexes show carbon resonances which are in the chemical shift range of known η 3 -allyl-type complexes 3 An ORTEP (50% probability ellipsoids) view of Co 2 (CO) 7 (Me 2 CCCH 2 ) 2 ( 1 ) as determined by X-ray diffraction.…”
Section: Resultsmentioning
confidence: 99%